A Meta-Analysis of 30 Years in China and Micro-District Experiments Shows Organic Fertilizer Quantification Combined with Chemical Fertilizer Reduction Enhances Rice Yield on Saline-Alkali Land - He Chen; Ruan Yunze; Jia Zhongjun (Rice Science)
To improve the yield and quality of rice grown on saline-alkali soil, a meta-analysis combined with micro-district experimental studies was conducted in China to examine the impact of humic acid- based organic fertilizer and chemical fertilizer on rice yield and quality. This study employed a two-factor fully randomized experimental design, incorporating four levels of humic acid (F0, 0.0 g/pot; F1, 4.8 g/pot; F2, 12.0 g/pot; and F3, 19.2 g/pot) and three levels of chemical fertilizer (A1, full conventional dosage; A2, 85% of conventional dosage; and A3, 70% of conventional dosage). The meta-analysis revealed that the application of organic fertilizer (at a rate of 1500‒3000 kg/hm2) combined with chemical fertilizer had a significantly positive effect on the theoretical yield, tiller number, partial factor productivity, and SPAD value of rice. Temperature, organic fertilizer application, and chemical fertilizer levels were identified as critical factors affecting rice yield. The micro-experiments demonstrated that the application of humic acid organic fertilizer with treatment F3 significantly elevated the SPAD value at the full heading and grain filling stages. Increased panicle number and seed-setting rate were the main contributors to the rise in yield, with the F3 treatment yielding the highest overall. The effective leaf area, high-efficiency leaf area, and dry matter accumulation in rice treated with F3 were all higher compared with the F0 treatment. Our findings indicated that the addition of humic acid organic fertilizer can markedly improve the partial factor productivity and agronomic efficiency of rice. In conclusion, the application of F3 organic fertilizer combined with A3 chemical fertilizer (F3A3) significantly increased the yield of saline-alkali rice, which was 6.62% higher than that of the F0A1 treatment, thereby validating the meta-analysis outcomes. We propose that the combined use of humic acid organic fertilizer and chemical fertilizer can promote the growth of rice in saline-alkali soils. Consequently, these management practices provide a means to foster the green and healthy development of rice in saline-alkali regions across China.